De la chose sensible à la chose esthétique Le passage de l’instrumentalisation à la configuration du monde (Itinera, 2023)
Through Heidegger’s re-reading of Descartes, this article explores a fundamental issue in the contemporary conception of worldliness. In a restricted sense, the human being is the maker of the world in that he appropriates what composes it, i.e., the worldly beings or things. Greatly influenced by the Cartesian notion of extensio, this tendency no longer entails the world as a thing in itself, but as a set of measurable things, thus available and open to activity.This article articulates the threat relative to the idea of the forming, by the human being, of the essence of the world. Every being, be it an object, an animal or even a human being, seems to be considered as a producer of energy and a structure that could be possessed. For example, such natural space is not campaign or land, but automatically field, that is to say, an agricultural deposit that is symbolically exploited and empirically exploitable. This ontological device prevents us from grasping the world in any other way than in terms of use and productivity.As a result, the ontology of the thing becomes an aesthetic issue in its own right. This issue does not involve here the capture of the object as a bearer of Beauty, but an aesthetic relation in the fundamentally etymological sense (αἰσθητικός) of what is felt, of what is sensible and perceptible. The need for an aesthetic rereading of the world and the things that stand in it presupposes, therefore, the evolution of the human gaze and a metaphysical approach to worldliness, detached from the instrumentalization of the beings and focused on their presence or their proximity. This article aims at demonstrating the necessity of a real human aesthetic responsibility, which can be concretized in the metaphysical thought of the thing that the human being unfolds, by considering it as the persistence in the world of an object whose ontological disposition could never be neutral.